Unveiling aging heterogeneities in human dermal fibroblasts via nanosensor chemical cytometry - Youngho Song; Inwoo Seo; Changyu Tian; Jiseon An; Seongcheol Park; Jiyu Hyun; Seunghyuk Jung; Hyun Su Park; Hyun-Ji Park; Suk Ho Bhang; Soo-Yeon Cho (Nature Communications)
Abstract Aging heterogeneity in tissue-regenerative cells leads to variable therapeutic outcomes, complicating quality control and clinical predictability. Conventional analytical methods relying on labeling or cell lysis are destructive and incompatible with downstream therapeutic applications. Here we show a label-free, nondestructive single-cell analysis platform based on nanosensor chemical cytometry (NCC), integrated with automated hardware and deep learning. nIR fluorescent single-walled carbon nanotube arrays in a microfluidic channel, together with photonic nanojet lensing, extract four key aging phenotypes (cell size, shape, refractive index, and H2O2 efflux) from flowing cells in a high-throughput manner. Approximately 105 cells are quantified within 1 h, and NCC phenotype data were used to construct virtual aging trajectories in 3D space. The resulting phenotypic heterogeneity aligns with RNA-sequencing gene-expression profiles, enabling reliable prediction of therapeutic efficacy. The platform rapidly identifies optimally aged cells without perturbation, providing a robust tool for real-time monitoring and quality control in regenerative-cell manufacturing.